Propylene glycol-induced lactic acidosis in a child receiving a pentobarbital continuous infusion - Chandler, Courtney J.; Cunnyngham, Christopher; Miller, Jamie; Johnson, Peter N. (Journal of Pediatric Intensive Care, 2014)
Pentobarbital (PB) contains 40% propylene glycol (PG) and could result in lactic acidosis (LA). Previous reports have indicated PG-induced LA following PB continuous infusion (CI), but there are no reports in young children. A 3-year-old male was admitted for new-onset seizures. After failing conventional therapy, he was initiated on intravenous PB on hospital day (HD) 3. The seizures continued, and he was initiated on a PB CI on HD 5 to achieve burst suppression. His CI was titrated to 10 mg/kg/hr. On HD 15, he developed hypotension with a mean arterial pressure (MAP) in the 40's and venous lactate of 3.01 mmol/L (normal range: 0.4–2.0 mmol/L). He received epinephrine, and his PB was decreased to 8 mg/kg/hr. Over the next few weeks, he continued to have subclinical seizures and PB was increased to 10 mg/kg/hr. On HD 37, he developed hypotension with a lactate of 6.28 and osmolar gap of 20.4 mOsm/kg. He received a fluid bolus, sodium bicarbonate, and his PB was decreased to 5 mg/kg/hr. His PB was tapered off, and the decision was made to treat clinical seizures only. The World Health Organization recommends a maximum of 25 mg/kg of PG. On HD 15 and 37, our patient received more than this threshold, 1398 and 1604 mg/kg, respectively. The Naranjo probability scale supports a high-probable drug-related adverse event. Practitioners should be aware of this potential adverse event with medications containing PG. Routine monitoring of osmolar gap should be performed for patients with prolonged use or higher PB doses.
Keywords: Pentobarbital; propylene glycol; children; lactic acidosis; pediatrics